Frontera política, resistencias y solidaridades: el caso de los refugiados de la Guerra Civil Española en Barrancos (1936) - Dulce Simões (Cahiers de Civilisation Espagnole Contemporaine)
The Spanish-Portuguese border was an instrument of protection and resistance, which demarcated the lives and deaths of thousands of people during the Spanish Civil War (1936-1939), despite Salazar having strengthened his control and surveillance. In the Portuguese village of Barrancos (Baixo Alentejo) two of the largest flows of Spanish refugees into Portuguese territory took place, made up of politically distinct groups. The reception of the Spanish neighbors justified the construction of a local social memory anchored in solidarity and resistance as identity factors. This problematic prompted me to question the ambiguities of the place of the border as a space of multiple powers, in order to understand the strategies of resistance and the border solidarities inserted in a macro level of political changes.